Complete mitochondrial genome of the marine polychaete, Marphysa sanguinea (Polychaeta, Eunicida). (2nd January 2016) - Li, Shilei; Chen, Yuan; Zhang, Ming; Bao, Xiangbo; Li, Yunfeng; Teng, Weiming; Liu, Zhongying; Fu, Chengdong; Wang, Qingzhi; Liu, Weidong
Abstract: The complete mitochondrial genome of Marphysa sanguinea from northern China was determined. This entire sequence was 15, 159 bp in length, containing 13 protein-coding genes (PCGs), 2 rRNA genes, 22 tRNA genes and a putative control region (D-loop). The base composition of the genome was 30.7% A, 30.3% T, 26.5% C and 12.6% G. Some PCGs shared nucleotides with neighboring genes, and all 13 PCGs had ATG as a start codon. Two complete stop codons (TAA, TAG) were used by the PCGs. Compared to other marine polychaetes and oligophaetes, most of the PCGS were without any rearrangement, except for ND2 and ND3, in which the order was reversed.